Perumusan Kebijakan Pengembangan Potensi Pengusaha Kecil Bidang Pariwisata dengan Analisis Hirarki Prioritas - Hamidah Nayati Utami (Fakultas Ilmu Administrasi Universitas Brawijaya (FIA UB))
Development process for community need intervention from outsider. They are the stakeholder of development, such as Local Government, NGO, University, Local Group, Local Leader, or Cooperation. The aim of this research was formulating policy of small business competency development on tourism. Research Location was Sendangbiru beach at East Malang. Using Analysis Hierarchy Priorities, the research collected the data from experts in these area: small business, tourism, human resource, and community development. The result of this research have main priority to developing competency with non-formal education from small business . The actor of small business development are Local government, NGO, University and Cooperation, they should have one coordination to develop small business. The competency area of small business are marketing, financial, ecology, and business diversification. Keyword: small business, tourism, competency, community development.